INDIGOFERA TINCTORIA LINN. STUDY OF TOTAL PROTEIN CONTENT OF PLANTS (Scientific journal of the Fergana State University, 2024)
The article examines the total protein content in the stem, grain and bean of the plant Indigofera tinctoria L.,belonging to the legume family (Fabaceae), grown in three different (fertile, saline, arid) climatic conditions of theFergana region. The Keldal method is used in the work – one of the generally recognized methods for determining thetotal protein content in the plant Indigofera tinctoria L. When determining the amount of protein in the samples by theKeldal method, the stages of hydrolysis with sulfuric acid, neutralization with sodium hydroxide and titration of theremaining acid with an alkali solution were carried out. The results obtained were compared with each other and with theamount of protein from other legumes. According to the results of the study, it was found that the grain of Indigoferatinctoria L. grown in arid conditions contains 25.967% protein, in the fruit box - 9.539%, in saline conditions - in the stemof the plant - 5.688%.